A study to assess the effect of planned teaching program on knowledge regarding misconceptions on blood donation among junior college students in the selected college of Sangli, Miraj, Kupwad corporation area. - Kulkarni, Sunil; Kulkarni, Manisha (International Journal of Nursing Research, 2023)
Blood transfusion help in improving health and saving the life of a patient, but many patients requiring transfusion do not have timely access to safe blood. Voluntary blood donation is considered as the backbone of blood safety and safe transfusion practices. Blood donations in India are conducted by several organizations and hospitals by organizing blood donation camps. Donors can also visit blood banks in hospitals to donate blood or directly to a receiver. Despite the shortage of donated blood, efforts by the government and various organizations have led to a decrease in the demand and supply gap over the years. Aim: To assess the existing knowledge on misconceptions regarding blood donation among junior college students in the selected college of Sangli, Miraj, Kupwad corporation area. To assess the effect of plan teaching on knowledge regarding misconceptions of blood donation among the junior college students in the selected college of Sangli, Miraj, Kupwad corporation area. Methods: The study was conducted in the junior college of Sangli, Miraj, Kupwad corporation area the population of the present study was junior college students of selected colleges from Sangli, Miraj, Kupwad Corporation Area. The sample size in this research was 138 junior college students. A pilot study was conducted from 19/09/17 to 25/09/17. This was done to assess the knowledge regarding the misconceptions about blood donation in the selected college of Sangli, Miraj, and Kupwad corporation area. Results: The mean pre-test knowledge score was 8.96 and post-test knowledge score of subjects was 11.53. Mean of post-test knowledge score was found to be significantly higher than mean pre-test knowledge score. The current study revealed that among the respondents the most prevalent misconception was that a blood donor has a risk of contracting infections like HIV or hepatitis B. Conclusion: The knowledge of blood donation was not up to the mark and many misconceptions ware prevailing among young students.